10-Formyl-2,4,6,8,12-pentanitro-2,4,6,8,10,12-hexaazatetracyclo[5.5.0.0(3,11).0(5,9)]dodecane - Jin, Shaohua (International Union of Crystallography, 2009)
The title compound, C(7)H(7)N(11)O(11) (PNMFIW), is a caged heterocycle substituted with five nitro and one formyl groups. It is related to the hexaazaisowurtzitane family of high-density high-energy polycyclic cage compounds. Four nitro groups are appended to the four N atoms of the two five-membered rings, while a nitro group and a formyl are attached to the two N atoms of the six-membered ring.